Designing interventions to address complex societal issues - Morton, Sarah, 1964- (New York, NY : Routledge, 2022)
"This edited volume is about the application of design-led approaches for developing interventions that have the intention of addressing real-world issues and problems. The book documents the realities of developing and designing interventions for real people, in a real-world context. The topics covered in the book are multi-disciplinary, and include examples from health and wellbeing, education, and agriculture. The contributors provide open and honest accounts of the challenges and restrictions, highlighting the positive impact that can be gained from involving stakeholders as key voices in the intervention development process. These case studies suggest underpinning methodologies that will support the formalisation of these design-led approaches, permitting the formation of robust frameworks in the future. The book will be of interest to scholars working in design, design research, intervention design, co-design, user-centred design, service design, digital design, digital healthcare, and evidence-based design"--
Introduction: Using design-led approaches to develop interventions with end-users : an overview of the realities in practice / Sarah Morton -- Person-centred technology for independent living : designing individualised participation-focused interventions / Duncan Pentland, Julie King, Gail Cairn-Levy -- Co-designed or evidenced based? Developing digital self-management interventions for long-term conditions / Claire McCallum Miglena Campbell, Kate Hackett, John Vines -- Targeted design for a specialist working population : how livestock veterinary surgeons inform the design of web-based interventions that support coping / Kate Stephen, Andrew Duncan -- Take a stand for workplace health : designing sit-stand desk interventions to reduce sitting and increase physical activity / Jennifer Hall, Louise Mansfield -- Designing innovation for health : the role of problem framing in Uganda / Leigh-Anne Hepburn -- Towards a shared understanding of genuine co-design with people with lived experience : reflections from co-designing for relational and transformational experiences in health and social care in the UK / Sneha Raman, Tara French -- Situating the Covid aware app : challenges of designing with predictive models / Larissa Pschetz , Arlene Bailey, Jonathan Rankin, Jessica Enright, Marisa Wilson -- Enhancing learning opportunities through experience via the design of an e-laboratory / William James Morton -- Futuring the entrepreneur : design as a pedagogic catalyst within sustainable entrepreneurship learning / George Jaramillo, Joe Lockwood -- Design-led approaches for responding to behaviour change : in the context of adventure sport / Sarah Morton -- Make space for girls : designing greenspace and other public spaces to reflect the needs of teenage girls / Amanda Seims, Susannah Walker, Imogen Clark, Sufyan Abid Dogra -- Designing beyond tokenism : transdisciplinary collaboration within the academy / Leigh-Anne Hepburn -- Reflections on chapters 2-13 : what can we learn from existing multidisciplinary practice, and what next? : Toward a framework for design-led practice for designing complex interventions to address societal issues / Sarah Morton, William James Morton.
Keywords: Design -- Human factors; Design -- Social aspects; Social action